Evaluation of color stability of different temporary restorative materials - José Vitor Quinelli Mazaro; Luiz Miguel Minani; Adriana Cristina Zavanelli; Caroline Cantieri de Mello; Cleidiel Aparecido Araújo Lemos
AbstractIntroductionTemporary restorative materials are widely used, however, little is know about their color stability.Objectiveto evaluate the color stability of the following temporary restorative materials: acrylic and bis-acrylic resins after immersion in pigmenting solutions for different periods of storage.Material and methodFour materials were tested (Dêncor/Clássico, Protemp 4/3M ESPE; Structur 2 SC/Voco; Luxatemp AM Plus/DMG) and 30 test specimens (15 mm in diameter and 2 mm thick) per material were fabricated. They were divided according to the storage medium (artificial saliva, saliva + cola type soda, and saliva + coffee) and storage time intervals (2, 5, 7 and 15 days). Color measurements were made before and after immersions, with use of a spectrophotometer, by means of the CIE L*a*b* system. The data were analyzed by the analysis of variance and the Tukey Test, at a level of significance of 5%.ResultAcrylic resin presented greater color stability in comparison with bis-acrylic resins (p<0.001). When bis-acrylic resins were compared no significant difference was observed between the resins Structur and Luxatemp (p=0.767). As regards solutions tested, coffee showed the highest color change values (p<0.001), and the longer the storage time interval, the greater was the color change in all the temporary restorative materials analyzed (p<0.001).ConclusionAcrylic resin presented greater color stability in comparison with bis-acrylic resins (p<0.001). Coffee caused the greatest color change, and immersion time was determinant in color stability of the temporary materials analyzed.